PERBANDINGAN BIAYA DAN WAKTU PEMBANGUNAN GEDUNG PASCASARJANA UPI DENGAN METODE MODULAR PADA DINDING - Ary Setyawan; Gabriella Angelisa Claudia; Fajar Sri Handayani (Program Studi Teknik Sipil FT UNS, 2025)
The Indonesian University of Education faced project delays that had an impact on the budget and timing of the Postgraduate Building's development. The UPI Postgraduate Building is being constructed using traditional methods, which results in a lengthy amount of work. The aforesaid issue might have a solution in the modular approach. The modular approach can swiftly meet significant customer demands since it has a production technique for creating components that are mass-produced. The conventional method's implementation costs and timeline are being contrasted with the modular method's implementation costs and timeline. The cost and construction time of traditional walls and modular walls which use precast concrete materials and lightweight concrete panels are compared for wall components. To make the optimal decision, the analysis was done using the comparison technique and the cost-effectiveness analysis approach. From the results of the analysis, the use of precast concrete and lightweight concrete panels experienced cost inefficiencies of 17.92% and 11.75% but were able to save time 62.03% and 34.78% respectively. Based on the Cost Effectiveness Analysis, an alternative material that was a more cost-effective choice was precast concrete walls.